The influence of audit committee characteristics on firm performance : evidence in Oman - Badhabi, Hussein Ahmed Saleh (2016)
The role of an audit committee (AC) is very significant to stakeholders in influencing the quality of disclosure of financial reporting and in improving market performance. This study examines the influence of audit committee characteristics (AC multiple directorship, AC size, AC independence, AC meeting, AC chairman independence, AC diligence) and firm performance (ROA and Tobin’s Q). The population of the study is 82 firms based on the Muscat Stock Market (MSM) listed companies as at 2014 to 2015, excluding the financial and banking sectors. The method of data collection was secondary data, using annual financial reports of firms gathered from Data Stream. The data was analyzed using Stata. The major findings of the study show that audit committee characteristics do not influence firm performance as measured by ROA. However, the study found that AC multiple directorships and AC diligence influence the firm performance as measured by Tobin’s Q. The result also showed that the control variables; (firm size and leverage) are significant in influencing firm performance (ROA and Tobin’s Q). Therefore, the study recommends future studies to consider taking into account some other variables such as foreign audit committee members, and other variables that may have a significant role in improving firm performance.